High angular momentum halo gas: a feedback and code-independent prediction of LCDM - Stewart, Kyle R.; Ceverino, Daniel; Oñorbe, Jose (The astrophysical journal, 2017)
We investigate angular momentum acquisition in Milky Way-sized galaxies by comparing five high resolution zoom-in simulations, each implementing identical cosmological initial conditions but utilizing different hydrodynamic codes: Enzo , Art , Ramses , Arepo , and Gizmo-PSPH . Each code implements a distinct set of feedback and star formation prescriptions. We find that while many galaxy and halo properties vary between the different codes (and feedback prescriptions), there is qualitative agreement on the process of angular momentum acquisition in the galaxy’s halo. In all simulations, cold filamentary gas accretion to the halo results in ∼4 times more specific angular momentum in cold halo gas ( λ cold ≳ 0.1) than in the dark matter halo. At z > 1, this inflow takes the form of inspiraling cold streams that are co-directional in the halo of the galaxy and are fueled, aligned, and kinematically connected to filamentary gas infall along the cosmic web. Due to the qualitative agreement among disparate simulations, we conclude that the buildup of high angular momentum halo gas and the presence of these inspiraling cold streams are robust predictions of Lambda Cold Dark Matter galaxy formation, though the detailed morphology of these streams is significantly less certain. A growing body of observational evidence suggests that this process is borne out in the real universe.